Effect of Fat and CHO Meals on Intermittent Exercise in Soccer Players - Hulton, A. T.; Edwards, J. P.; Gregson, W.; MacLaren, D.; Doran, D. A. (International Journal of Sports Medicine, 2013)
Pre-exercise meals containing carbohydrates (CHO) are recommended to athletes, although there is evidence to suggest that a high fat meal prior to exercise increases utilisation of fats yet may not adversely affect performance. This study investigated the effect of a high fat and high CHO pre-exercise meal prior to high intensity intermittent exercise. Ten male recreational soccer players performed a soccer specific protocol followed by a 1 km time trial 3 ½ h after ingesting one of 2 test meals, high fat meal (HFM) or a high CHO meal (HCM). Blood glucose, fatty acids (FA), glycerol, β-hydroxybutyrate, lactate and insulin were assessed prior to the meal, pre-exercise, half-time, and post-exercise, whilst rates of CHO and fat oxidation were determined at 4 time points during the exercise as well as heart rate (HR) and rating of perceived exertion (RPE). Significant increases in FA, glycerol, β-hydroxybutyrate and fat oxidation after the HFM were observed, while CHO oxidation was significantly higher following the HCM (P<0.05). No performance effect was found for the 1 km time trial (HFM: 228.6+14.4 s; HCM: 229.4+26.5 s) (mean+SD). These findings suggest that the type of meal ingested prior to soccer simulated exercise has an impact on metabolism, but not on the subsequent performance as determined in the present study.
Keywords: high fat meals; pre-exercise meals; intermittent exercise; association football